Distribution of Traditional Irrigation Canals and Their Discharge Dynamics at the Southern Slopes of Mount Kilimanjaro - Kimaro, Jerome G.; Scharsich, Valeska; Kolb, Andreas; Huwe, Bernd; Bogner, Christina (Frontiers in Environmental Science, 2019)
On the southern slopes of Mt.\ Kilimanjaro like in many other regions in East Africa, agriculture strongly depends on irrigation. Water is supplied to farms by an extensive network of open unlined canals, most of them built centuries ago. However, information about the distribution of these irrigation canals and the dynamics of their discharge is rare thus hampering the implementation of sustainable solutions for agricultural water management. We suppose that several factors like topography, soil properties, shifts of cropping patterns and weak institutions affect availability and management of agricultural water. Therefore, in this study we determined (i) the distribution of irrigation canals (ii) their discharge patterns and (iii) constraints to their sustainable management. The discharge of canals was measured at 11 locations along an altitudinal gradient and selected canals were mapped to understanding their distribution, physical characteristics and potential risks that limits their optimal discharge. Terrain attributes were derived from the ASTER DEM image and soil physical and hydraulic conductivity were measured to understand permeability and stability of the soil. Additionally, we conducted focus group discussions with participants from 15 villages and 10 key informants interviews. We found that the discharge of canals increased with decreasing elevation. The median daily discharges equalled 12.6, 9.5 and 7.0 l/s in the lower, mid and upper areas, respectively. During the dry season the discharge of canals was higher than in the short rainy season. Landscape in the central part of the study area was the steepest $(slope > 60%)$ and the roughest $(Topographic Ruggedness Index > 80~m)$ which affects the distribution of canals and their maintenance. Furthermore, current shifts of cropping patterns increased irrigation water demands. Both formal and informal water institutions were constrained with several challenges that affected overall management of canals and their sources. Distribution and discharge of canals at Mt.\ Kilimanjaro are influenced by both biophysical and anthropogenic activities. Therefore, integrated approaches are needed to achieve equitable and sustainable supply of water among different user groups.